ANALISIS PENERAPAN PRINSIP-PRINSIP PELATIHAN TEKNIS TERHADAP PENCAPAIAN INDIKATOR KINERJA PEGAWAI DI KANTOR SEKRETARIAT DAERAH PEMERINTAH KABUPATEN MAJENE (Studi Kasus pada Kantor Sekretariat Daerah Kab. Majene) - Wahdaniah -; Wahyu Maulid Adha (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, This research aims to know how big the influence of application of technical training principles toward the official work of Majene District Regional Secretariat Office. This research was ex post facto research. The sample of this research was the employee of Majene District Regional Secretariat Officewho participated the technical training which followed by 84 participants. The data was collected by using questionnaire and documentation. The questionnaire used for measuring the variable of application of technical training principles and the official work, while documentation used for advocating the research data. The data analysis technique used was prerequisite test analysis with linear test, and hypothesis test used was simple regression analysis. The research result indicated that application of technical training principles had positive influence and significant toward the official work and the influence was on the average category which shown by the similarity regression Y = 0,220X + 12,885 with the coefficient regression (rxy) was 0,840, coefficient determination (r2xy) was 0,705 and found thitung was 14,009 bigger than ttabel1,663. Based on the coefficient determination (r2xy) 0,705 which mean 70,5% the official work was influenced by education and training employee while the rest 29,5% was influenced by others variable which were not being researched in this study.